2015
DOI: 10.1182/blood-2015-02-629204
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous cytogenetic subgroups and outcomes in childhood acute megakaryoblastic leukemia: a retrospective international study

Abstract: Comprehensive clinical studies of patients with acute megakaryoblastic leukemia (AMKL) are lacking. We performed an international retrospective study on 490 patients (age £18 years) with non-Down syndrome de novo AMKL diagnosed from 1989 to 2009. Patients with AMKL (median age 1.53 years) comprised 7.8% of pediatric AML. Five-year event-free (EFS) and overall survival (OS) were 43.7% 6 2.7% and 49.0% 6 2.7%, respectively. Patients diagnosed in 2000 to 2009 were treated with higher cytarabine doses and had bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
66
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 37 publications
5
66
0
1
Order By: Relevance
“…A Cox regression analysis was performed for EFS, OS, and for the probability of relapse-free survival (RFS) considering the following covariables: cytogenetic subgroup, age, sex, white blood cell (WBC) count at diagnosis, and HSCT (as time-dependent variable), as well as the previously described poor prognostic factors for pediatric AMKL "normal karyotype" and monosomy 7. 11,24,25 Furthermore, we included a hyperdiploid karyotype and 7p-abnormalities in the Cox regression analysis, based on the association with pediatric AMKL. 11,26,27 Statistical analysis was restricted to groups with .5 cases.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…A Cox regression analysis was performed for EFS, OS, and for the probability of relapse-free survival (RFS) considering the following covariables: cytogenetic subgroup, age, sex, white blood cell (WBC) count at diagnosis, and HSCT (as time-dependent variable), as well as the previously described poor prognostic factors for pediatric AMKL "normal karyotype" and monosomy 7. 11,24,25 Furthermore, we included a hyperdiploid karyotype and 7p-abnormalities in the Cox regression analysis, based on the association with pediatric AMKL. 11,26,27 Statistical analysis was restricted to groups with .5 cases.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…11,24,25 Furthermore, we included a hyperdiploid karyotype and 7p-abnormalities in the Cox regression analysis, based on the association with pediatric AMKL. 11,26,27 Statistical analysis was restricted to groups with .5 cases. Statistical significance was considered if P values were ,.05.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…AMKL in children without DS is The outcomes for this class of AMKL vary among the different genetic subtypes, but on average, the 5-year event-free survival and overall survival were reported to be 43% and 49%, respectively. 67 In contrast, the genetic basis of adult AMKL is poorly defined and the outcome is dismal, with a median survival of 10.4 months. 68 Of note, children with DS-AMKL fare well, with 5-year event-free survival and overall survival approaching 80%.…”
mentioning
confidence: 99%
“…They also confirm, using sequencing methods, the poor prognosis imparted by monosomy 7 reported by Inaba and colleagues using traditional karyotyping in their landmark retrospective study of 490 pediatric AMKL patients in the International BFM (I-BFM) Study Group. 4 The molecular confirmation of poorprognosis lesions reported in this study will undoubtedly generate additional hypotheses about the role of associated fusions in the unique pathogenesis of myelomegakaryocytic differentiation and fuel the search for druggable targets. For example, several groups, including the authors of this study, have already reported a role for NUP98 fusion oncoproteins in dysregulated HOX gene expression as a proleukemogenic event in AML.…”
mentioning
confidence: 99%